A novel strategy to simultaneously enhance bioaccessible lipids and antioxidants in hetero/mixotrophic Chlorella vulgaris as functional ingredient. (March 2022) - Canelli, Greta; Tevere, Sabrina; Jaquenod, Luc; Dionisi, Fabiola; Rohfritsch, Zhen; Bolten, Christoph J.; Neutsch, Lukas; Mathys, Alexander
Graphical abstract: Highlights: Nitrogen starvation triggered the accumulation of fatty acids and α-tocopherol. Mixotrophic growth enhanced carotenoid and phenolic contents in C. vulgaris. Lutein was the most abundant carotenoid in C. vulgaris. Pulsed electric field improved the bioaccessibility (BA) of lipids and carotenoids. High pressure homogenization improved the BA of lipids, carotenoids and phenolics. Abstract: Microalgae are a promising source of polyunsaturated fatty acids as well as bioactive antioxidant compounds such as carotenoids, phenolics and tocopherols. However, the accumulation of these biomolecules is often promoted by conflicting growth conditions. In this study, a phased bioprocessing strategy was developed to simultaneously enhance the lipid and antioxidant amounts by tailoring nitrogen content in the cultivation medium and applying light stress. This approach increased the overall contents of total fatty acids, carotenoids, phenolics, and α-tocopherol in Chlorella vulgaris by 2.2-, 2.2-, 1.5-, and 2.1-fold, respectively. Additionally, the bioaccessibility of the lipids and bioactives from the obtained biomasses improved after pulsed electric field (5 μs, 20 kV cm −1, 31.8 kJ kg −1 sus ) treatment (up to +12%) and high-pressure homogenization (100 MPa, 5–6 passes) (+41–76%). This work represents a step towards the generation of more efficient algae biorefineries, thus expanding the alternative resources available for essential nutrients.